Cover Image, Volume 529, Issue 14. Issue 14 (22nd July 2021) - Jacob, Joanna; Kent, Molly; Benson‐Amram, Sarah; Herculano‐Houzel, Suzana; Raghanti, Mary Ann; Ploppert, Emily; Drake, Jack; Hindi, Bilal; Natale, Nick R.; Daniels, Sarah; Fanelli, Rachel; Miller, Anderson; et al.
Abstract : The cover image is based on the Research Article Cytoarchitectural characteristics associated with cognitive flexibility in raccoons by Joanna Jacob et al., https://doi.org/10.1002/cne.25197 .